2021
DOI: 10.3390/jcm10112510
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Fetal Arrhythmias

Abstract: Fetal arrhythmias are mostly benign and transient. However, some of them are associated with structural defects or can cause heart failure, fetal hydrops, and can lead to intrauterine death. The analysis of fetal heart rhythm is based on ultrasound (M-mode and Doppler echocardiography). Irregular rhythm due to atrial ectopic beats is the most common type of fetal arrhythmia and is generally benign. Tachyarrhythmias are diagnosed when the fetal heart rate is persistently above 180 beats per minute (bpm). The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 84 publications
(255 reference statements)
0
21
0
Order By: Relevance
“…We searched the PubMed, Web of Science, Medline, Embase, and Cochrane Library databases to identify studies comparing and evaluating the effects of various drug regimens used to regulate fetal tachycardias from database inception to July 2021, with no limits on the study design, country of origin, tachycardia type, administration route (placental, intravenous, intramuscular or other administration routes), or whether combination treatment was applied. Additional studies for inclusion were identified from among the references of relevant reviews ( Alsaied et al, 2017 ; Hill et al, 2017 ; Carvalho, 2019 ; Yuan, 2020 ; Veduta et al, 2021 ). The search strategy was established previously, and the terms included digoxin; flecainide; sotalol; amiodarone; tachycardia(s); fetus; supraventricular tachycardia or SVT; and atrial flutter or AF.…”
Section: Methodsmentioning
confidence: 99%
“…We searched the PubMed, Web of Science, Medline, Embase, and Cochrane Library databases to identify studies comparing and evaluating the effects of various drug regimens used to regulate fetal tachycardias from database inception to July 2021, with no limits on the study design, country of origin, tachycardia type, administration route (placental, intravenous, intramuscular or other administration routes), or whether combination treatment was applied. Additional studies for inclusion were identified from among the references of relevant reviews ( Alsaied et al, 2017 ; Hill et al, 2017 ; Carvalho, 2019 ; Yuan, 2020 ; Veduta et al, 2021 ). The search strategy was established previously, and the terms included digoxin; flecainide; sotalol; amiodarone; tachycardia(s); fetus; supraventricular tachycardia or SVT; and atrial flutter or AF.…”
Section: Methodsmentioning
confidence: 99%
“…Most fetal arrhythmias are benign and transient, but persistent fetal arrhythmia can cause fetal deterioration. Among them, fetal supraventricular tachycardia often responds to fetal therapy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal supraventricular tachycardia can be controlled by transplacental administration of anti-arrhythmic drugs such as digoxin, flecainide, sotalol, and, more rarely, amiodarone. Fetal therapy is the recommended management to sufficiently decrease the ventricular rate in order to achieve a good cardiac output for fetuses with hydrops or at high risk of developing hydrops such as those with sustained tachycardia with ventricular rates > 200 bpm [ 1 ]. A recent meta-analysis on the transplacental treatment of fetal tachycardia showed that both flecainide and sotalol were more effective than digoxin for conversion of any fetal tachycardia to sinus rhythm, especially in cases of fetal hydrops [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is also a valid option for fetuses with AF not associated with ASA, since postnatal treatment of tachyarrhythmia is usually effective. There is little reason to pursue transplacental drug therapy for the term fetus with tachyarrhythmia but no hydrops [ 33 ].…”
Section: Discussionmentioning
confidence: 99%